INNOVATION PROCESS OF NATURAL-RESOURCE-BASED FIRMS IN FOUR ASEAN ECONOMIES: AN SEM APPROACH - Masatsugu Tsuji; Hiroki Idota; Yasushi Ueki; Teruyuki Bunno (STI Policy and Management Journal, 2017)
This paper focuses on natural-resource-based firms in four ASEAN economies, such as Vietnam, Indonesia, The Philippines, and Thailand. These countries have relative advantage in natural-resource-based industries, since they have affluent endowed resources and been making use them for their export and growth strategies. In this study, the innovation process in natural-resource-based industries in these countries are examined in comparison with other assembling and processing industry by focusing factors enhance product as well as process innovation. Those are summarized as (i) Technology, (ii) Organization learning including QM, cross functional team, (iii) ICT use, and (iv) external linkages such as MNCs, local and public organizations, universities. This study employs SEM (Structural equation model) in order to analyze the causal relationships not only among above four latent variables but also between these and innovations.Keywords: internal capability, external linkage, organization learning, capital goods, ICT use, SEM (Structural equation model)